1990
DOI: 10.1029/ja095ia05p06375
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of the subsolar magnetopause for northward IMF: ISEE observations

Abstract: Detailed magnetopause structure and properties for the magnetic field, electric field and plasma are examined for an ISEE 1 magnetopause crossing which occurred near the subsolar point when the interplanetary magnetic field (IMF) was strongly northward. Because the crossing is slow, the spatial variations in the plasma are clearly resolved. This example illustrates the nature of the steady state interface of two magnetized thermal plasma populations with parallel fields and can serve as a guide to theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
74
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 44 publications
14
74
1
Order By: Relevance
“…Although previous studies have demonstrated that enhanced amounts of plasma enter to form a relatively thick, lowlatitude boundary layer 2,12,13 and a denser plasma sheet 13,14 when the IMF is northward even during quiet times, the dominant mechanism of solar wind entry into the magnetosphere (and entry location on the magnetopause) under these conditions is less clear and still controversial. It is still not very clearly understood whether the entering plasma is a result of the highlatitude MR 12,[15][16][17][18][19][20][21][22] , impulsive penetration 23,24 , or from the low latitudes through instabilities 25,26 or gradient drift 27 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Although previous studies have demonstrated that enhanced amounts of plasma enter to form a relatively thick, lowlatitude boundary layer 2,12,13 and a denser plasma sheet 13,14 when the IMF is northward even during quiet times, the dominant mechanism of solar wind entry into the magnetosphere (and entry location on the magnetopause) under these conditions is less clear and still controversial. It is still not very clearly understood whether the entering plasma is a result of the highlatitude MR 12,[15][16][17][18][19][20][21][22] , impulsive penetration 23,24 , or from the low latitudes through instabilities 25,26 or gradient drift 27 .…”
mentioning
confidence: 98%
“…T he Earth is one of the six solar system planets that have global magnetic fields 1 , which are sufficient to block and deflect most solar wind charged particles from the Sun's atmosphere, and prevent them from directly interacting with the atmosphere of the planet 2,3 . This shielding is thought to be one of the most important factors protecting life on the ground and spacecraft in geospace from being damaged 4,5 .…”
mentioning
confidence: 99%
“…Gary and Eastman (1979) proposed lower hybrid drift (kinetic) instability as a drive diffusive process for LLBL. However, the transition from magnetosheath to the boundary layer is often thin (less than an ion's gyroradius) and the plasma within the boundary layer is uniform, suggesting that diffusion is not important Song et al, 1990;Le et al, 1994). Another local entry mechanism, impulsive penetration, was proposed by Lemaire and Roth (1978), Lemaire (1985) and Ross (1992).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic topology of the LLBL is still unclear. Song et al (1993) found that under northward IMF, the inner (earthward) part of the LLBL is on closed magnetic field lines, whereas the outer part could be composed of open and closed field lines. Fuselier et al (1995) suggested that the LLBL could be on open field lines.…”
Section: Introductionmentioning
confidence: 99%
“…Pashmann et al, 1993;Song et al, 1993). Absence of magnetic flux pile-up is thus also interpreted as a consequence of the open structure of the MP (e.g.…”
Section: Introductionmentioning
confidence: 99%